SIFAT-SIFAT TANAH YANG BERKEMBANG DARI BAHAN VOLKAN DI HALMAHERA BARAT, MALUKU UTARA - Hikmatullah Hikmatullah (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2010)
[SOIL PROPERTIES DEVELOPED FROM VOLCANIC MATERIALS IN WEST HALMAHERA, NORTH MALUKU]. West Halmahera region is dominated by soils formed from young volcanic materials that have unique properties and high productivity for agricultural use. The purpose of this study is to characterize soil properties derived from volcanic materials in that area and to test the andic soil properties according to Soil Taxonomy 2006. Four pedons of strato volcanoes from the area were described their morphological properties in the field and 16 soil samples were analyzed for physical, chemical and mineralogical properties in the laboratory. The results indicated that all the pedons show black to very dark brown colored in A horizons and dark brown to brown in B horizons. The soils are deep, loam to sandy loam texture (sand content 38-71 %). The soils have weak to moderate subangular blocky structure and very friable consistency. The soils show slightly acid to neutral reaction (pHH2O 6.0-6.8), high pHNaF (10.78-10.95), high organic carbon (3.75-4.65 %) in A horizon, moderate to high cation exchange capacity and base saturation. All the pedons show high P-retentions (45-80 %), high values of ammonium oxalate extractable (Alo+0.5Feo) (2.91-6.070 %), high volcanic glass content (>5%), and index values of [(Alo+0,5Feo) x 15,625+ (%volcanic glass)] > 36.25 that meet the requirements for andic soil properties, and thus they are classified as Andisols order. The sand minerals are dominated by volcanic glasses and dark minerals that belong to intermediary properties, and high weatherable mineral reserve.